Устойчивый дайв-туризм в России - Bautista, H.; Orekhova, A. A.; Mustafin, M. R.; Баутиста, Х.; Орехова, А. А.; Мустафин, М. Р. (Тюменский государственный университет, 2022)
The article examines the Russian territorial natural complexes for diving in terms of their infrastructural, natural and other advantages and disadvantages. Russia as the largest country in the world and is surrounded not only by European and Asian states, but also by large oceanic water areas, including the Pacific and Arctic oceans. Russia attracts fans of such sports as diving from all over the world, the water resources offer a whole new world, with mysterious caves, sunken ships, many marine animals and fish. This significant volume which conceptualizes the issues surrounding scuba diving tourism now and in the future is a valuable reading for all those interested in Russian marine leisure and tourism.In this article, we will highlight the top five diving spots in Russia. В статье рассмотрены российские территориально-природные комплексы для дайвинга в аспекте их инфраструктурных, естественно-природных и иных преимуществ и недостатков. Россия является крупнейшей страной мира и окружают её не только европейские и азиатские государства, но и большие океанические водные пространства, в том числе Тихий и Северный Ледовитый океаны. Россия привлекает любителей такого спорта, как дайвинг, со всего мира; водные ресурсы России скрывают в себе целый новый мир, с таинственными пещерами, затонувшими кораблями, множеством морских животных и рыб. Значительный объем информации, который концептуализирует вопросы, связанные с подводным туризмом сейчас и в будущем, является ценным чтением для всех тех, кто заинтересован в российском морском досуге и туризме. В данной статье мы расскажем о пяти главных местах для занятий дайвингом в России.